Bahaya Praktik Riba dan Etika Upaya Pencegahannya - Niken Lestari; Adam Surya (Lembaga Penelitian dan Pengembangan Masyarakat IAINU Kebumen, 2021)
In the context of providing handling in dealing with the dangers of usury , business ethics or morals in doing business are necessary. Because in doing business it's not only related horizontally, that is, to fellow human beings, but in all business it is also required to have a good relationship vertically vertically. These business ethics include the principles of faith and piety, intentions that are sincere, virtuous, noble, lawful business, fulfilling rights, learning manners and practicing Islamic muammalah, avoiding all transactions that are prohibited by the Shari'a, including riba, and keeping commitments. Ethics in business is really needed for business people, because in doing business we don't only think about profits but more about the common good, so that all parties will feel benefited without exception.